The Support Role in Clinical Supervision of Nursing Students: Determinant in the Development of Emotional Skills - Diogo, P (2016)
The problematic situation faced by clients, associated to the processes of health and disease, is expressed through emotions that nursing students have to deal with in the course of care and their formative experiences in clinical teaching. Students have learning needs not only to manage emotions in the context of customer care, but also in terms of their own internal world, emotional conflicts, emotional stress and burn-out. With the present literature review, we intend to explore existing evidence regarding the ways in which the nurse supervisor's support towards nursing students potentiates the development of their competences for the performance of emotional labour. These skills prove to be the key in the ability to manage the emotionally intense situations of care practice and the support function of the nursing supervisor contributes to the development of such competences.